Volatile aroma compounds in wines from Chinese wild/hybrid species. Issue 10 (21st September 2018) - Wei, Zheng; Liu, Xihua; Huang, Yu; Lu, Jiang; Zhang, Yali
Abstract: The volatile aroma compounds in wines produced from Chinese wild/hybrid species were investigated in comparison to wines from European grapes. Volatiles were extracted by headspace solid‐phase micro‐extraction and identified by gas‐chromatography/mass‐spectrometry. The identification of analyte was performed by a combination of the linear retention index approach with the comparison of the obtained mass spectra. A total of 98 peaks were tentatively assigned as wine aroma components, and 15 odorants can be found at concentrations above their odor threshold among the odor activity values (OAVs) of 46 compounds evaluated in all of the wines. The "OAVs' aroma wheels" showed that the classes of aromatic series are first fruity, next herbaceous and roasty and no spicy and caramelized notes. Via principal component analysis, all the grape germplasm studied could be divided into four groups: "Jingsheng‐1, " "Cabernet Gernischt, " "Beibinghong, " and others, which exhibited distinctive aroma features, respectively. Practical applications Chinese wild grape species have many desirable properties for wine grape breeding such as possessing strong resistant genes to fungal diseases and cold condition, especially after hybridization with European grapes. As an emerging wine country, wines from Chinese wild/hybrid species have achieved much success in the last few years. The chemical content and biological properties have been studied extensively in many but there are a few studies in our knowledge about the wine tastes of these species. In this paper, the key odorants in wines produced from the Chinese grape species of V. amurensis Rupr., V. davidii Foex., and V. quinquangularis Rehd. and its hybrids were characterized in comparison to wines produced from European grapes ( V. vinifera ). The findings will help to the further understanding of the key aroma components in the different Chinese grapevine germplasm, and make further efforts to enrich the wine types in the marketplace.